RISK FACTORS AND EPIDEMIOLOGY OF ACUTE AND RECURRENT OBSTRUCTIVE BRONCHITIS IN CHILDREN - Turakulova , Hilola; Azizova , Nigora (International Journal of Scientific Pediatrics, 2023)
Diseases of the respiratory system remain one of the urgent problems in pediatrics in terms of morbidity and complications among children. Acute asthma and bronchitis, which are often observed in young children, can lead to negative consequences when observed with broncho-obstructive syndrome. The growing trend of acute respiratory diseases in children and their role in the development of broncho-obstructive syndrome, relapses of obstructive bronchitis, the high frequency of recurrent bronchitis and the high risk of developing bronchial asthma indicate the need for further study of the disease. Among the factors leading to the development of broncho-obstructive syndrome, respiratory infections are observed in 5-40% of cases and occupy a leading place. Purpose of the study. Risk factors for the development of broncho-obstructive syndrome and their distribution in the conditions of the Ferghana Valley of Uzbekistan. Research methods and materials. An epidemiological analysis was carried out using statistical methods to assess risk factors for the development of broncho-obstructive syndrome. The anamnesis of children aged 1 to 18 years hospitalized in 2017-2021 was analyzed. to the department of "Pulmonology" of the Andijan Regional Children’s Multidisciplinary Medical Center. In a retrospective study, a total of 6965 patients were examined, of which 1208 (17%) were diagnosed with broncho-obstructive syndrome. 1208 patients diagnosed with broncho-obstructive syndrome were divided into 3 nasological groups: 1- group: 966 people (80%) with acute community-acquired broncho-obstructive syndrome. 2-group of acute obstructive bronchitis 72 people (6%), 3- group of recurrent obstructive bronchitis 170 people (14%). Results of the study and their discussion. A retrospective analysis of the disease history shows the presence of various risk factors in the development of symptoms of respiratory failure, frequent observation of RD and a high risk of developing bronchial asthma, the coexistence of background diseases, and age differences. According to the data obtained, the symptoms of bronchial obstruction were observed in all children. Based on a retrospectively analyzed history, acute obstructive bronchitis was detected in 942 (78%) children with frequent acute respiratory infections (6 times or more) during the year, in 290 (24%) with diseases of the ENT organs, in 318 (26.3%) with allergic conditions. , 273 (22.6%) formula-fed children, 832 (68.9%) cases of maternal anemia, 824 (68.2%) cases of complicated pregnancy. Conclusion. Predisposing factors and risk factors for the development of broncho-obstructive syndrome: severe pregnancy, anemia in the mother, asphyxia during childbirth, artificial feeding of the child, allergic tendency of the body, frequent acute respiratory infections, pathologies of ENT organs, protein-energy deficiency. , hereditary and congenital diseases of the respiratory system.